Vida longa, longa vida - desafios da longevidade: grupo psicoterapêutico para mulheres na terceira idade - Schalch, Maria de Lourdes Soares (2010)
The change of the age standard in population shows us the world growing up in a universe of large and rapid changes. The population gets old and needs to maintain good quality of life for this stage of vital cycle that was previously not so representative. Through experience with groups of activities aimed at this population, was observed there was an opportunity to invest in psychotherapy for the elderly in order to provide better conditions to stand up against crises characteristic of aging, that reflects on routine s matters , such as technological, physical, social and emotional changes, their concerns, fears, challenges, what they think of third age, their difficulties, their plans, how they picture their future, how they see themselves, and finally how they evaluate the group of therapy, the much that helped in their problems, what were the achievements resulting from participation in the group. The current work aims to study the possibility and validity of conducting a group therapy for women in old age. Therefore it was proposed the fulfillment for a group with people who was interested and was already participating in the group of living in the Health Unit. They were invited to join the work of psychotherapy. Such a decision is taken because of the prejudice against the execution of psychotherapy for the elderly and the lack of services aimed at this population. The work follows two years, and to participate in the study, the volunteers should attend the group at least four months. Semi-structured interviews were made and also Genograms to qualitatively evaluate the benefit of performing such work. According to the result aimed at this group, we could emphasize contributions to the improvement of quality of life in the participants, and recommend the conduct of psychotherapy for women in old age in other health services